Kartläggning av klimatarbete och klimatkrav i elnätsbranschen - Blomberg, Marcus (SLU/Dept. of Energy and Technology, 2022)
The climate change is a growing issue that is put high up on the agenda for countries as well as businesses. In 2015 both EU and Sweden initiated joint initiatives to actively promote reduction of climate impact and stop the increase in global temperature. A part of the solution is electrification, which requires comprehensive investment in both new and old electric networks. The purpose of this master thesis was to examine how Ellevio as an electric grid owner can reduce their climate impact using requirements within the tender offer in procurements. The report should also work as a basis for the development of future requirements. This was done through a field study based on interviews with frequently used contractors and suppliers. Following the compilation of the interviews, an internal workshop was also held in which benefits, disadvantages and implementation were discussed for selected ideas from the interviews. The study has shown that there is widespread interest within the electricity network industry to reduce climate impact, but it also emerged that there is significant spread in both knowledge and focus as well as in the work mapping and reducing their impact. The larger companies interviewed tended to have climate targets established and actively worked to reduce their climate impact while smaller companies had less knowledge and less structured work. The study also showed that there was a greater awareness of reducing the climate impact among producing companies compared to contractors and that most of them worked on the development of measurement tools and programs for climate impact. The solutions reducing climate impacts identified through the study has been dominated by methods and strategies linked to documentation and administrative procedures to use within the procurement more than concrete requirements for emisson reduction. One reason for this has been lack of knowledge of climate impact within the sector along with absence of established communication routes regarding greenhouse gas emissions. One solution identified in the study, is to establish requirements within the tender offer that companies must include a description of their work reducing climate impact based on preidentified areas. Appropriate areas identified is climate impact from materials, circular use of construction machines and materials, waste management and resource efficacy management strategy. Furthermore, the next step would be to require accounting for climate calculations for the areas above. Another solution is to, within selected projects, work with deeper cooperation with contractors and to promote internal and external knowledge development regarding climate impact. One option would be to certify the selected projects with a CEEQUAL-certification, which is a type of sustainability certification of projects. By doing so, the development of cooperation with entrepreneurs in the climate impact area should increase, the possibility to get support from a third party who are familiar with both the work process and climate impact mitigation work is also a great benefit. For the procurement of cable, which takes place both in the form of framework contracts and project-specific, it has not been possible to establish a clear recommended route forward, but that further investigation in this area must take place due to the fact that most emission derives from it, and that the future investigations should focus on the the areas logistics, energy use, climate calculations and climate impact from material production.